2012
DOI: 10.1093/nar/gks209
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide polycomb target gene prediction in Drosophila melanogaster

Abstract: As key epigenetic regulators, polycomb group (PcG) proteins are responsible for the control of cell proliferation and differentiation as well as stem cell pluripotency and self-renewal. Aberrant epigenetic modification by PcG is strongly correlated with the severity and invasiveness of many types of cancers. Unfortunately, the molecular mechanism of PcG-mediated epigenetic regulation remained elusive, partly due to the extremely limited pool of experimentally confirmed PcG target genes. In order to facilitate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 104 publications
(164 reference statements)
0
28
0
1
Order By: Relevance
“…Algorithms based on clustered consensus binding sites for PRE DNA binding proteins have been marginally successful in identifying PREs, giving both false positive and false negative results (Fiedler & Rehmsmeier, 2006; Ringrose et al, 2003; Zeng, Kirk, Gou, Wang, & Ma, 2012). In one study, of 167 potential PREs that Ringrose et al (2003) identified, only 16% of them were PcG binding sites in PcG ChIP genome-wide studies of Drosophila embryos (Schuettengruber et al, 2009).…”
Section: Pres In Drosophilamentioning
confidence: 99%
“…Algorithms based on clustered consensus binding sites for PRE DNA binding proteins have been marginally successful in identifying PREs, giving both false positive and false negative results (Fiedler & Rehmsmeier, 2006; Ringrose et al, 2003; Zeng, Kirk, Gou, Wang, & Ma, 2012). In one study, of 167 potential PREs that Ringrose et al (2003) identified, only 16% of them were PcG binding sites in PcG ChIP genome-wide studies of Drosophila embryos (Schuettengruber et al, 2009).…”
Section: Pres In Drosophilamentioning
confidence: 99%
“…In Drosophila, Polycomb response elements (PREs)-with a combination of motifs for a number of transcription factors (TFs) such as PHO, GAGA factor (GAF), and zeste-have been implicated in PRC2 recruitment (Ringrose et al 2003;Schuettengruber et al 2009). Although binding of PHO is indeed observed in nearly all Polycomb domains (Schuettengruber et al 2009), methods to predict PREs based on these motifs perform very poorly (Zeng et al 2012). In vertebrates, PRE sequences remain largely elusive.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…Thus, despite the unambiguous genetic and genomic evidence for PREs, and for the involvement of PHO and DSP1 in their function, the specificity of the process remains difficult to understand based on studies of individual factors or loci. Thus far, any attempts to predict PREs from genomic sequence alone have only been partly successful (Fiedler and Rehmsmeier, 2006;Kassis and Brown, 2013;Ringrose et al, 2003;Zeng et al, 2012).…”
Section: Introductionmentioning
confidence: 99%